Simultaneous measurement of malondialdehyde, formaldehyde, acetaldehyde, and propionaldehyde to monitor the oxidative stress in humans - Kanďár, Roman; Drábková, Petra; Richter, Milan; Rusnoková, Marcela; Čegan, Alexander (University of Pardubice, 2015)
Herein, a method is described for the determination of malondialdehyde, formaldehyde, acetaldehyde, and propionaldehyde in human plasma. Plasma sampleswere obtained fromblood donors. After protein precipitation, the samples were derivatized with 2,4-dinitrophenylhydrazine and repeatedly extracted with pentane. So combined pentane extracts were evaporated to dryness, under nitrogen atmosphere, and the dried residue was re-suspended in acetonitrile. Aliquots of 20 μl in acetonitrile were injected onto a LichroCART 125-4, Purospher STAR RP-18e, 5 μm column. The derivatives were analysed with the aid of gradient elution, when using a mobile phase containing acetonitrile, water, and acetic acid. The analytical performance of this method has been found to be satisfact ory characterised by the intra-assay coefficients of variation below 12 % and quantitative recoveries as follows: 98.3 % (CV 1.6%) for malondialdehyde, 104.4 % (CV 4.0 %) for formaldehyde, 96.9 % (CV 3.0 %) for acetaldehyde, and 105.9 % (CV 1.7 %) for propionaldehyde.